Nano-emulsion, preparation method thereof and working fluid system containing nano-emulsion
By using nanoemulsion as fracturing working fluid in shale oil extraction and using low molecular weight polyacrylamide as thickener for sand carrying liquid, the problems of poor sand carrying capacity and formation damage in the existing technology are solved, and the problem of Highly efficient and low-damage shale oil fracturing effect.
Patent Information
- Application Number
- CN202311011244.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-08-11
AI Technical Summary
The existing shale oil extraction technology has poor sand carrying capacity, difficulty in transporting proppant, excessive sand ratio leads to sand blockage or excessive sand ratio leads to low sand laying concentration in the crack and small diversion capacity, which affects the fracturing effect.
A nanoemulsion is used as the pre-liquid, sand-carrying liquid and depolymerization liquid for fracturing working fluid. The nanoemulsion is composed of benzenesulfonic acid polybutadiene, first anionic surfactant, long-chain alkyl compound, monophenyl Compounds and water are composed of low molecular weight polyacrylamide as thickener for sand carrying liquid, and after fracturing, depolymerization agent is injected into depolymerization agent to degrade polyacrylamide, reducing damage to the formation.
The shale oil fracturing effect without residues and low friction is achieved, which improves the protection of the reservoir, enhances the oil washing efficiency, and reduces the damage of the fracturing fluid to the formation.
Abstract
Description
Technical Field
[0001] The invention relates to the field of petroleum exploitation, and in particular to a nanoemulsion used for shale oil exploitation. Background Art
[0002] With the gradual consumption and depletion of conventional oil and gas resources around the world and the increasing demand for energy for economic and social development, unconventional resources are receiving more and more attention and importance.
[0003] Shale oil refers to the oil resources contained in shale formations dominated by shale. It is an important unconventional oil and gas resource and a potential substitute for traditional oil resources. Shale oil includes oil in the pores and cracks of mudstone, as well as oil resources in the adjacent layers and interlayers of dense carbonate or clastic rocks in mudstone formations.
[0004] Usually, effective development methods are horizontal wells and staged fracturing technology. However, existing fracturing technology has the following disadvantages: poor sand carrying capacity, difficulty in proppant transportation, and sand plugging easily caused by too high sand ratio, while too low sand ratio will lead to low sand concentration in the fracture and low fracture conductivity, which will affect the fracturing effect. Therefore, the performance of pre-flushing fluid and fracturing fluid is improved. That is, pre-flushing fluid is first injected to flush the wellbore to ensure good cementing quality, which is the prerequisite for achieving fracturing construction, and then the fracturing working fluid with strong sand carrying capacity is injected to carry the proppant to the fracture to improve the fracture conductivity.
[0005] In the field of solid minerals, shale oil is a kind of artificial petroleum, which is a brown, viscous liquid product with a special pungent smell generated by the thermal decomposition of organic matter during shale distillation. China's continental basins contain huge shale oil resource potential, with an estimated recoverable resource volume of (30-60)×10 8 Tons. The latest exploration and development results show that my country has drilled industrial oil flow wells in many regions, indicating that shale oil has great potential for exploitation; however, due to the unique physical properties of mud shale reservoirs, such as its extremely low porosity and permeability, shale oil has difficulty flowing in tight reservoirs, and mud shale reservoirs are easily damaged by external working fluids, which makes shale oil generally have low single-well production and rapid production decline, making it difficult to form an industrial scale; compared with the high cost of shale oil exploitation, the current production is far from the standard of economic benefits, so shale oil exploitation depends on effective artificial fracturing and fracture technology to improve the physical properties of shale oil reservoirs to promote the flow of shale oil. In particular, the shale oil reservoir of Shengli Oilfield reaches more than 6,000 meters, and the exploitation of shale oil depends on effective fracturing technology, which puts higher requirements on cementing and completion technology. Summary of the invention
[0006] One of the present inventions provides a nanoemulsion, which includes benzenesulfonic acid-based polybutadiene, a first anionic surfactant, a long-chain alkyl compound, a monophenyl compound and water.
[0007] In a specific embodiment, the weight average molecular weight of the benzenesulfonate polybutadiene is 2,000 to 3,000.
[0008] In a specific embodiment, the first anionic surfactant is at least one of sodium dodecyl sulfate, dodecylbenzene sulfonic acid, anionic polyacrylamide, fatty acid salts, sulfonates, sodium fatty alcohol sulfate, and sulfates; the long-chain alkyl compound is at least one of butane, hexane, pentane and heptane; and the monophenyl compound is at least one of toluene, ethylbenzene and xylene.
[0009] In a specific embodiment, based on 100 parts by mass of water, the amount of the benzenesulfonic acid polybutadiene is 30 to 35 parts by mass, the amount of the first anionic surfactant is 0.1 to 0.2 parts by mass, and the total amount of the long-chain alkyl compound and the monophenyl compound is 3 to 5 parts by mass.
[0010] In a specific embodiment, the mass ratio of the long-chain alkyl compound to the monophenyl compound is 1:4 to 4:1.
[0011] The second aspect of the present invention provides a method for preparing the nanoemulsion according to any one of the first aspects of the present invention, comprising the following steps:
[0012] 1) mixing benzenesulfonic acid polybutadiene and water evenly, adding a first anionic surfactant, mixing evenly, and standing to obtain a pre-hydration treatment solution;
[0013] 2) uniformly mixing the pre-hydration treatment liquid, the long-chain alkyl compound and the monophenyl compound to obtain the nanoemulsion.
[0014] In one embodiment, in step 1), the mixture is mixed at 50 to 70° C. and allowed to stand at natural ambient temperature.
[0015] In one embodiment, the standing time is 20 to 24 hours.
[0016] The third aspect of the present invention provides a shale oil fracturing working fluid system, which includes independently constructed pre-fluid, sand-carrying fluid and depolymerization fluid, wherein:
[0017] The pre-liquid is a nanoemulsion as described in any one of the first invention or a nanoemulsion prepared by the preparation method described in the second invention;
[0018] The sand-carrying fluid comprises polyacrylamide, a second anionic surfactant and water;
[0019] The depolymerization liquid comprises a depolymerization agent, a third anionic surfactant and water.
[0020] In a specific embodiment, the weight average molecular weight of the polyacrylamide is 100,000 to 120,000.
[0021] In a specific embodiment, the depolymerizing agent is di-tert-butyl peroxide and / or benzoyl peroxide.
[0022] In a specific embodiment, based on 100 parts by mass of water in the sand-carrying fluid, the amount of the polyacrylamide used is 0.11 to 0.17 parts by mass, and the amount of the second anionic surfactant used is 0.1 to 0.2 parts by mass.
[0023] In a specific embodiment, based on 100 parts by mass of water in the depolymerization liquid, the amount of the depolymerization agent is 0.11 to 0.17 parts by mass, and the amount of the third anionic surfactant is 0.1 to 0.2 parts by mass.
[0024] In a specific embodiment, the second anionic surfactant and the third surfactant are independently at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecylbenzene sulfonic acid, anionic polyacrylamide, fatty acid salts, sulfonates, sodium fatty alcohol sulfates and sulfates.
[0025] Beneficial effects of the present invention:
[0026] With the exploration and development of shale oil in oil fields, low permeability, ultra-low permeability, and complex sensitive reservoirs are gradually increasing. Conventional guar gum fracturing fluid will leave a large amount of residue in the cracks and crack walls during the fracturing construction process, causing reservoir damage, resulting in reduced formation seepage capacity and reduced production capacity, which directly affects the fracturing effect. Reducing the amount of thickener will reduce the content of solid phase substances entering the formation, and can effectively reduce the damage of fracturing fluid filtrate and residues to cracks and reservoirs. The present invention uses low molecular weight polyacrylamide as a sand-carrying fluid thickener. After the fracturing filling is completed, a depolymerizing agent is injected to degrade the polyacrylamide. Under the premise of ensuring crack formation and sand carrying, the damage of the fracturing fluid to the matrix supporting the cracks and crack walls is minimized. Therefore, the present invention provides a residue-free, low-friction, high-efficiency, low-damage, low-molecular weight polyacrylamide clean sand-carrying fluid, which greatly improves reservoir protection and is of great significance.
[0027] Since the currently used emulsion has a large particle size and a large adsorption loss, it is difficult to improve the oil washing efficiency of emulsion flooding in low permeability oil reservoirs. Therefore, it is urgent to develop an oil washing system that is suitable for cleaning well wall oil stains with a nanoemulsion pre-washing liquid, a small particle size, and a high oil washing efficiency. The nanoemulsion of the present invention has an obvious imbibition oil displacement effect and can be used as a pre-flushing liquid for cleaning well walls. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation methods do not constitute limitations of the present invention under any circumstances.
[0029] Benzenesulfonate polybutadiene was purchased from Evonik Degussa.
[0030] Nanoemulsion
[0031] Example 1
[0032] 100 parts by mass of water were measured and heated to 50°C. Under 5000 r / min electric stirring, 30 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 2000 was added. After stirring for 10 minutes (first stirring), 0.125 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand for 24 hours at natural ambient temperature for prehydration treatment. The mixture was heated to 50°C and 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 1:1) were added under low speed 1000 r / min electric stirring. The mixture was then stirred for 20 minutes (third stirring) under 5000 r / min electric stirring to prepare the nanoemulsion.
[0033] Example 2
[0034] 100 parts by mass of water were measured and heated to 60°C. Under 3000 r / min electric stirring, 30 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 2000 was added. After stirring for 10 minutes (first stirring), 0.125 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand for 24 hours at natural ambient temperature for prehydration treatment. The mixture was heated to 60°C and 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 1:1) were added under low speed 1000 r / min electric stirring. The mixture was then stirred for 20 minutes (third stirring) under 3000 r / min electric stirring to prepare the nanoemulsion.
[0035] Example 3
[0036] 100 parts by mass of water were measured and heated to 60°C. Under 3000 r / min electric stirring, 35 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 2000 were added. After stirring for 10 minutes (first stirring), 0.125 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand for 24 hours at natural ambient temperature for prehydration treatment. The mixture was heated to 60°C and 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 1:1) were added under low speed 1000 r / min electric stirring. The mixture was then stirred for 20 minutes (third stirring) under 3000 r / min electric stirring to prepare the nanoemulsion.
[0037] Example 4
[0038] 100 parts by mass of water were measured, and the temperature was raised to 60°C. Under 3000 r / min electric stirring, 30 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 2000 was added. After stirring for 10 minutes (first stirring), 0.1 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand at natural ambient temperature for 24 hours for prehydration treatment. Then, 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 1:1) were added under low speed 1000 r / min electric stirring, and then the mixture was stirred for 20 minutes (third stirring) under 3000 r / min electric stirring to prepare the nanoemulsion.
[0039] Example 5
[0040] 100 parts by mass of water were measured and heated to 60°C. Under 3000 r / min electric stirring, 30 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 2000 was added. After stirring for 10 minutes (first stirring), 0.2 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand for 24 hours at natural ambient temperature for prehydration treatment. The mixture was heated to 60°C and 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 1:1) were added under low speed 1000 r / min electric stirring. The mixture was then stirred for 20 minutes (third stirring) under 3000 r / min electric stirring to prepare the nanoemulsion.
[0041] Example 6
[0042] 100 parts by mass of water were measured and heated to 60°C. Under 3000 r / min electric stirring, 30 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 3000 were added. After stirring for 10 minutes (first stirring), 0.125 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand for 24 hours at natural ambient temperature for prehydration treatment. The mixture was heated to 60°C and 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 4:1) were added under low speed 1000 r / min electric stirring. The mixture was then stirred for 20 minutes (third stirring) under 3000 r / min electric stirring to prepare the nanoemulsion.
[0043] Example 7
[0044] 100 parts by mass of water were measured and heated to 60°C. Under 3000 r / min electric stirring, 30 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 2000 was added. After stirring for 10 minutes (first stirring), 0.125 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand for 24 hours at natural ambient temperature for prehydration treatment. The mixture was heated to 60°C and 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 1:4) were added under low speed 1000 r / min electric stirring. The mixture was then stirred for 20 minutes (third stirring) under 3000 r / min electric stirring to prepare the nanoemulsion.
[0045] Example 8
[0046] 100 parts by mass of water were measured and heated to 70°C. Under 2000 r / min electric stirring, 30 parts by mass of benzenesulfonic acid polybutadiene with a weight average molecular weight of 2000 was added. After stirring for 10 minutes (first stirring), 0.125 parts by mass of sodium dodecyl sulfate was added. After stirring for another 10 minutes (second stirring), the mixture was allowed to stand for 24 hours at natural ambient temperature for prehydration treatment. The mixture was heated to 70°C and 3.0 parts by mass of heptane and toluene (wherein the mass ratio of heptane to toluene was 1:1) were added under low speed 1000 r / min electric stirring. The mixture was then stirred for 20 minutes (third stirring) under 2000 r / min electric stirring to prepare the nanoemulsion.
[0047] Sand carrying fluid
[0048] Example 9
[0049] 100 parts by mass of water were measured, and at natural ambient temperature, 0.11 parts by mass of polyacrylamide with a weight average molecular weight of 120,000 was added under electric stirring at 2000-5000 r / min. After stirring for 10 minutes (first stirring), 0.2 parts by mass of sodium dodecyl sulfate was added, and after stirring for another 10 minutes (second stirring), the sand-carrying liquid was prepared.
[0050] Example 10
[0051] 100 parts by mass of water were measured, and at natural ambient temperature, 0.15 parts by mass of polyacrylamide with a weight average molecular weight of 120,000 was added under electric stirring at 2000-5000 r / min. After stirring for 10 minutes (first stirring), 0.1 parts by mass of sodium dodecyl sulfate was added, and then stirred for another 10 minutes (second stirring) to prepare the sand-carrying liquid.
[0052] Embodiment 11
[0053] Measure 100 parts by mass of water, add 0.17 parts by mass of polyacrylamide with a weight average molecular weight of 120,000 under natural ambient temperature and electric stirring at 2000-5000r / min, stir for 10 minutes (first stirring), then add 0.1 parts by mass of sodium dodecyl sulfate, stir for another 10 minutes (second stirring), and the sand-carrying liquid is prepared.
[0054] Example 12
[0055] Measure 100 parts by mass of water, add 0.11 parts by mass of polyacrylamide with a weight average molecular weight of 100,000 under electric stirring at 2000-5000r / min at natural ambient temperature, stir for 10 minutes (first stirring), then add 0.2 parts by mass of sodium dodecyl sulfate, stir for another 10 minutes (second stirring) to prepare the sand-carrying liquid.
[0056] Embodiment 13
[0057] Measure 100 parts by mass of water, add 0.17 parts by mass of polyacrylamide with a weight average molecular weight of 100,000 under natural ambient temperature and electric stirring at 2000-5000r / min, stir for 10 minutes (first stirring), then add 0.1 parts by mass of sodium dodecyl sulfate, stir for another 10 minutes (second stirring), and the sand-carrying liquid is prepared.
[0058] Depolymerization solution
[0059] Embodiment 14
[0060] 100 parts by mass of water was measured, and 0.11 parts by mass of di-tert-butyl peroxide was added under electric stirring at 2000-5000 r / min at natural ambient temperature. After stirring for 10 minutes (first stirring), 0.2 parts by mass of sodium dodecylbenzene sulfonate was added, and after stirring for another 10 minutes (second stirring), the depolymerization liquid was prepared.
[0061] Embodiment 15
[0062] 100 parts by mass of water was measured, and at natural ambient temperature, 0.15 parts by mass of di-tert-butyl peroxide was added under electric stirring at 2000-5000 r / min. After stirring for 10 minutes (first stirring), 0.1 parts by mass of sodium dodecylbenzene sulfonate was added, and after stirring for another 10 minutes (second stirring), the depolymerization liquid was prepared.
[0063] Example 16
[0064] 100 parts by mass of water was measured, and 0.17 parts by mass of di-tert-butyl peroxide was added under electric stirring at 2000-5000 r / min at natural ambient temperature. After stirring for 10 minutes (first stirring), 0.1 parts by mass of sodium dodecylbenzene sulfonate was added, and after stirring for another 10 minutes (second stirring), the depolymerization liquid was prepared.
[0065] Embodiment 17
[0066] 100 parts by mass of water was measured, and 0.11 parts by mass of benzoyl peroxide was added under electric stirring at 2000-5000 r / min at natural ambient temperature. After stirring for 10 minutes (first stirring), 0.2 parts by mass of sodium dodecylbenzene sulfonate was added, and after stirring for another 10 minutes (second stirring), the depolymerization liquid was prepared.
[0067] Embodiment 18
[0068] 100 parts by mass of water was measured, and 0.15 parts by mass of benzoyl peroxide was added under electric stirring at 2000-5000 r / min at natural ambient temperature. After stirring for 10 minutes (first stirring), 0.1 parts by mass of sodium dodecylbenzene sulfonate was added, and after stirring for another 10 minutes (second stirring), the depolymerization liquid was prepared.
[0069] Embodiment 19
[0070] 100 parts by weight of water was measured, and 0.17 parts by weight of benzoyl peroxide was added under electric stirring at 2000-5000 r / min at natural ambient temperature. After stirring for 10 minutes (first stirring), 0.2 parts by weight of sodium dodecylbenzene sulfonate was added, and after stirring for another 10 minutes (second stirring), a depolymerization liquid was prepared.
[0071] Performance measurement
[0072] 1. Determination of the particle size of nanodroplets in nanoemulsions
[0073] The particle sizes of the nanodroplets in the nanoemulsions prepared in Examples 1 to 8 were measured using a laser scattering system (DLS), and the median particle sizes were obtained. The results are shown in Table 1.
[0074] According to the results in Table 1, the particle sizes of the nanodroplets in the nanoemulsions prepared in Examples 1 to 8 were measured, and the median particle sizes were found to be between 40 and 100 nanometers.
[0075] 2. Determination of interfacial tension
[0076] The nanoemulsions prepared in Examples 1 to 8 were diluted with water to 0.5 wt %, that is, 0.5 g of the nanoemulsion was mixed with 99.5 g of water, stirred evenly at 80° C. at a stirring speed of 5000 r / min, and then allowed to stand at 80° C. for 30 minutes to obtain a diluted nanoemulsion.
[0077] The interfacial tension of the diluted nanoemulsion was measured using a spinning drop interfacial tension meter. The results are shown in Table 1.
[0078] According to the results in Table 1, the nanoemulsions of Examples 1 to 8 exhibit good interfacial tension reduction performance. Low interfacial tension can effectively reduce the adhesion work between the oil phase and the rock surface and enhance the oil washing ability.
[0079] 3. Dispersion stability determination
[0080] The nanoemulsions prepared in Examples 1 to 8 were diluted with water to 0.5 wt %, that is, 0.5 g of the nanoemulsion was mixed with 99.5 g of water to obtain a diluted nanoemulsion. The diluted nanoemulsions were left to stand for 3 days at natural ambient temperature and 80° C. to observe whether the diluted nanoemulsions were separated or precipitated. The results are shown in Table 1.
[0081] According to the results in Table 1, the median particle size of the emulsion is between 40 and 100 nanometers, the minimum interfacial tension is 2.0 mN / m, and the emulsion has good stability without stratification or precipitation.
[0082] Table 1
[0083] Example Median particle size / nm Interfacial tension / mN / m Whether to layer Is precipitation produced? Example 1 40 4.0 no no Example 2 45 3.5 no no Example 3 43 3.0 no no Example 4 55 2.0 no no Example 5 61 2.5 no no Example 6 81 2.6 no no Example 7 90 3.3 no no Example 8 100 4.8 no no
[0084] 4. Oil displacement effect
[0085] 4.1 Oil displacement effect at different dilutions
[0086] The nanoemulsion prepared in Example 1 was diluted with water to 0.1 wt %, 0.2 wt %, 0.3 wt %, 0.4 wt % and 0.5 wt %, and stirred evenly at 80° C. at a stirring speed of 5000 r / min to obtain diluted nanoemulsions.
[0087] The core (core length 5.0 cm, diameter 2.5 cm) whose porosity and permeability had been measured in advance was vacuum-pressurized and saturated with formation crude oil (room temperature viscosity 0.7 MPa.s, density 0.713 g / cm 3 ), record the weight of the core before saturation with formation crude oil, the difference between the two is the weight of formation crude oil adsorbed by the core M1, and then age in a constant temperature box at 80°C for more than 24 hours. The saturated core is wrapped with copper wire and placed in water and diluted nanoemulsions of various concentrations for an imbibition experiment at 80°C for 2 hours, and the weight of the diluted nanoemulsion before and after imbibition is measured. The difference between the two is the weight of the washed formation crude oil M2. According to the formula, oil washing efficiency = M2 / M1×100%, the results are shown in Table 2.
[0088] Table 2
[0089] Diluted nanoemulsion Porosity <![CDATA[Permeability / 10 -3 μm 2 > Oil washing efficiency 0 9.3% 1.80 21.00% 0.1% 10.1% 0.59 35.12% 0.2% 7.3% 0.19 46.32% 0.3% 7.8% 0.12 55.06% 0.4% 8.0% 0.22 60.88% 0.5% 8.6% 0.32 60.12%
[0090] 4.2 Oil displacement effect of nanoemulsions in different embodiments
[0091] The nanoemulsions prepared in Examples 1 to 8 were diluted with water to 0.4 wt %, respectively, and stirred evenly at 80° C. at a stirring speed of 5000 r / min to obtain diluted nanoemulsions.
[0092] The oil washing efficiency of each nanoemulsion was determined using the same operation as in Section 4.1 above. The results are shown in Table 3.
[0093] Table 3
[0094] Example Porosity <![CDATA[Permeability / 10 -3 μm 2 > Oil washing efficiency Example 1 7.3% 0.19 61% Example 2 7.3% 0.19 62% Example 3 7.3% 0.19 58% Example 4 7.3% 0.19 56% Example 5 7.3% 0.19 63% Example 6 7.3% 0.19 68% Example 7 7.3% 0.19 70% Example 8 7.3% 0.19 54%
[0095] 5. Degradation rate determination
[0096] The sand-carrying liquid of Example 9 and the depolymerization liquid of Example 14 were mixed at a mass ratio of 1:1. After being mixed evenly, the mixture was placed at 50° C. for 24 h to obtain a degradation liquid. The residue was observed. The results are shown in Table 4.
[0097] The sand-carrying liquid of Example 10 and the depolymerization liquid of Example 15 were mixed in a mass ratio of 1:1, and degradation was carried out under the same conditions as above to obtain a degradation liquid. The residue was observed. The results are shown in Table 4.
[0098] The sand-carrying liquid of Example 11 and the depolymerization liquid of Example 16 were mixed in a mass ratio of 1:1, and degradation was carried out under the same conditions as above to obtain a degradation liquid. The residue was observed. The results are shown in Table 4.
[0099] The sand-carrying liquid of Example 12 and the depolymerization liquid of Example 17 were mixed in a mass ratio of 1:1, and degradation was carried out under the same conditions as above to obtain a degradation liquid. The residue was observed. The results are shown in Table 4.
[0100] The sand-carrying liquid of Example 13 and the depolymerization liquid of Example 18 were mixed in a mass ratio of 1:1, and degradation was carried out under the same conditions as above to obtain a degradation liquid. The residue was observed. The results are shown in Table 4.
[0101] The sand-carrying liquid of Example 9 and the depolymerization liquid of Example 19 were mixed in a mass ratio of 1:1, and degradation was carried out under the same conditions as above to obtain a degradation liquid. The residue was observed. The results are shown in Table 4.
[0102] Prepare polyacrylamide aqueous solutions with gradient concentrations, measure the peak area using high performance liquid chromatography, and draw a standard curve of polyacrylamide concentration.
[0103] The concentration of polyacrylamide in the above degradation solutions was determined by high performance liquid chromatography according to the above standard curve, and then the degradation rate of polyacrylamide was calculated based on the concentration of polyacrylamide in each degradation solution. The results are shown in Table 4.
[0104] Table 4
[0105] Example Example Observe the residue Degradation rate Example 9 Embodiment 14 none 80% Example 10 Embodiment 15 none 85% Embodiment 11 Example 16 none 90% Example 12 Embodiment 17 none 81% Embodiment 13 Embodiment 18 none 79% Example 9 Embodiment 19 none 75%
[0106] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.
Claims
1. A nanoemulsion comprising benzenesulfonate-based polybutadiene, a first anionic surfactant, a long-chain alkyl compound, a monophenyl compound and water.
2. The nanoemulsion according to claim 1, characterized in that The benzenesulfonic acid polybutadiene has a weight average molecular weight of 2,000 to 3,000.
3. The nanoemulsion according to claim 1, characterized in that The first anionic surfactant is at least one of sodium dodecyl sulfate, dodecylbenzene sulfonic acid, anionic polyacrylamide, fatty acid salts, sulfonates, sodium fatty alcohol sulfate and sulfates; The long-chain alkyl compound is at least one of butane, hexane, pentane and heptane; The monophenyl compound is at least one of toluene, ethylbenzene and xylene.
4. The nanoemulsion according to claim 1 or 2, characterized in that Based on 100 parts by mass of water, the amount of the benzenesulfonic acid polybutadiene is 30 to 35 parts by mass, the amount of the first anionic surfactant is 0.1 to 0.2 parts by mass, and the total amount of the long-chain alkyl compound and the monophenyl compound is 3 to 5 parts by mass.
5. The nanoemulsion according to any one of claims 1 to 4, characterized in that The mass ratio of the long-chain alkyl compound to the monophenyl compound is 1:4 to 4:
1.
6. A method for preparing a nanoemulsion according to any one of claims 1 to 4, comprising the steps of: 1) mixing benzenesulfonic acid polybutadiene and water evenly, adding a first anionic surfactant, mixing evenly, and standing to obtain a pre-hydration treatment solution; 2) uniformly mixing the pre-hydration treatment liquid with the long-chain alkyl compound and the monophenyl compound to obtain the nanoemulsion; Preferably, in step 1), the mixture is mixed at 50 to 70° C. and allowed to stand at natural ambient temperature; Preferably, the standing time is 20 to 24 hours.
7. A shale oil fracturing working fluid system, comprising independently constructed pre-fluid, sand-carrying fluid and depolymerization fluid, wherein: The pre-liquid is a nanoemulsion according to any one of claims 1 to 4 or a nanoemulsion prepared by the preparation method according to claim 5 or 6; The sand-carrying fluid comprises polyacrylamide, a second anionic surfactant and water; The depolymerization liquid comprises a depolymerization agent, a third anionic surfactant and water.
8. The shale oil fracturing working fluid system according to claim 7, characterized in that: The weight average molecular weight of the polyacrylamide is 100,000 to 120,000; and / or The depolymerizing agent is di-tert-butyl peroxide and / or benzoyl peroxide.
9. The shale oil fracturing working fluid system according to claim 7, characterized in that: Based on 100 parts by mass of water in the sand-carrying fluid, the amount of the polyacrylamide is 0.11 to 0.17 parts by mass, and the amount of the second anionic surfactant is 0.1 to 0.2 parts by mass; and / or Based on 100 parts by weight of water in the depolymerization liquid, the amount of the depolymerization agent used is 0.11 to 0.17 parts by weight, and the amount of the third anionic surfactant used is 0.1 to 0.2 parts by weight.
10. The shale oil fracturing working fluid system according to claim 7, characterized in that: The second anionic surfactant and the third surfactant are independently at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecylbenzene sulfonic acid, anionic polyacrylamide, fatty acid salt, sulfonate, sodium fatty alcohol sulfate and sulfate.
Citation Information
Patent Citations
Oil-gas well cementing spacer fluid having effect of protecting oil and gas reservoir
CN104745156A
Resistance reducing agent for fracture and preparation method thereof
CN104974308A
Turbid liquid type drag reducer and preparation method and application thereof
CN112410013A
Nano-emulsion composition, nano-emulsion, preparation method of nano-emulsion, anti-coagulation viscosity reducer for fracturing fluid and preparation method of anti-coagulation viscosity reducer
CN113004881A
Leaking stoppage and channeling prevention cleaning fluid
CN115873571A